2023
DOI: 10.3151/jact.21.248
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Damage Spatiotemporal Distribution in Saturated Cementitious Materials and its Chloride Transport Evolution

Abstract: Crack-induced damage significantly affects the chloride transport mechanism in cementitious materials. To quantitatively evaluate the crack effects, a coupled model was proposed in this paper for saturated cement paste with various uniaxial tensile damage. First, the 3D microstructure of hydrating cement paste was simulated based on a voxel-based hydration model, and its damaged spatiotemporal distribution under uniaxial tensile stress was simulated using a finite-element model. Based on the damaged cement pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The results showed that naturally formed cracks obtained through mechanical loading methods can be utilized to analyze the impact of morphological parameters, such as crack tortuosity and connectivity, on chloride erosion. The currently main used methods for mechanically generating cracks can be divided into four-point bending method [32,33], center expansion method [27], splitting method, and Wedge splitting method [34,35]. It should be noted, however, that cracks obtained through mechanical loading methods are influenced by loading conditions and material properties, and the characteristics of these cracks exhibit greater discretization.…”
Section: Crack-inducing Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that naturally formed cracks obtained through mechanical loading methods can be utilized to analyze the impact of morphological parameters, such as crack tortuosity and connectivity, on chloride erosion. The currently main used methods for mechanically generating cracks can be divided into four-point bending method [32,33], center expansion method [27], splitting method, and Wedge splitting method [34,35]. It should be noted, however, that cracks obtained through mechanical loading methods are influenced by loading conditions and material properties, and the characteristics of these cracks exhibit greater discretization.…”
Section: Crack-inducing Methodsmentioning
confidence: 99%
“…[30], © Elsevier Ltd., 2012; (c) four-point bending method [32,33], reproduced with permission from Ref. [32], © ASCE, 2011; (d) center expansion method [27]; (e) splitting method [4,24]; and (f) Wedge splitting method [34,35], reproduced with permission from Ref. [34], © RILEM, 2007.…”
Section: Many Scholars Have Conducted Experimental Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, anionic AWAs exhibit superior strength development, attributable to their temporally regulated cement hydration. This contrasts with the uncontrolled pore structure modifications induced by nonionic stabilization [50]. Manipulating the ionic character and solubility of AWAs has emerged as a promising route for balancing the demands of underwater concrete rheology, setting, and structural performance.…”
Section: Compressive Strengthmentioning
confidence: 99%
“…Sulfate, carbonation, freeze–thaw, and other problems caused by the deterioration of concrete can lead to many economic losses and safety hazards. The use of deicing salts can lead to corrosion of reinforcing steel in the concrete, which can also increase the deterioration of the concrete. It is estimated that of the more than 617,000 bridges currently owned by the United States, 42% are at least 50 years old, and 46,154 (7.5%) are considered deficient. As the condition of bridges continues to deteriorate, more bridges will need repair each year. In China, the problem of aging concrete structures is also very serious.…”
Section: Introductionmentioning
confidence: 99%